Designing a secured audio based key generator for cryptographic symmetric key algorithms - Avinash Krishnan Raghunath; Dimple Bharadwaj; M Prabhuram; Aju D (Institute of Advanced Engineering and Science, 2021)
Cryptography is a technique to secure data transmissions and ensure confiden-tiality, authenticity and integrity of data exchanged over the digital networks by utilizing mathematical algorithms to transform the plain text (original message) to cipher text (encrypted message) using a key or seed value. The general con-sensus regarding the use of non-deterministic true random numbers (TRN) which are generated from the physical environment such as entropy keys, at-mospheric noise, etc., as a public or private key has received limited encour-agement due to the demanding hardware requirements needed to extract the necessary data from the environment. Therefore, this research aims at design-ing and developing a lightweight program to generate a true random number (TRNG) key using live audio recordings which is further randomized using system date and time. These TRNs can be used to replace the deterministic pseudo random number cryptographic keys that are presently used by indus-tries for a symmetric key encryption algorithm which devolves the algorithm to being conditionally secured. Using the audio based TRNG key would render the same encryption algorithm as unconditionally secured.